Compact Multiantenna. (7th February 2012) - Rudant, L.; Delaveaud, C.; Ciais, P.
Abstract : Planar inverted-f antenna (PIFA) and notch antenna are combined within a compact 2-port MIMO antenna. Electrical and magnetic duality of the two antennas avoids a critical coupling and best performances can be expected for multiple-input multiple-output (MIMO) communication. When excitation of notch antenna is optimized properly, the notch length can be short enough so that the two antennas can be colocated in a single compact volume. This compact multiantenna design is suitable for integration in MIMO handheld terminals. A prototype for broadband network application in 3.4–3.8'GHz frequency band has been characterized in anechoic chamber.